Diseño organizacional y funcional para la empresa “Grupo Inloba” del Cantón Catamayo, Provincia de Loja - Bravo Vásquez, Santiago Alejandro (2023)
Through the introduction of this research work, the reader will be able to have a general idea of what has been carried out, the field of study, the purpose of developing this project and the benefits gotten when carrying out an analysis of its organizational and functional design. Both the general objective and the specific ones planned in the project had the purpose of covering all the aspects that can integrate an organizational design, for this reason it was necessary to collect data from primary sources, which helped to obtain information about the organizational culture of Grupo Inloba, as well as the structure it has, which later had to be reflected in the organizational charts that display the hierarchical levels and the degree of authority that the company possesses. The functions developed by the employees were also analyzed and using this information, some manuals will be used in order to avoid duplication of tasks; In the same way, it was possible to determine that there is no a welcome manual, which will provide the new employees the information about the company and who is part of it. The procedure manuals that were designed for the company are the following: production process, personnel selection, acquisitions and training, since there were none. The methodology used to carry out the research was explanatory, with a quantitative and qualitative approach, accompanied by a deductive and inductive, mathematical and statistical method, and with the help of research techniques and instruments such as the survey and observation, it was possible to collect enough data to set the organizational design. As conclusions, it can be mentioned that all the aforementioned objectives were accomplished, as the recommendations it is suggested that the managers of the company adopt the proposal, improving this way their internal and external image.